DETERMINING A TYPE OF A DAMAGE IN THE CURRENT PROTECTION OF POWER LINES OF 6–35 KV - F. A. Romaniuk; E. V. Buloichik; O. A. Huryanchyk; M. A. Shevaldin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods to identify types of phase-to-phase short circuits that can be used to improve technical excellence by speed-current line protection of distribution networks of 6–35 kV are considered. As a result of the assessment of the appropriateness of their application in current protection, the choice was made in favor of the method based on the control of the relative current unbalance. The influence of contact resistances and load currents of various levels on the magnitude and character of the change of relative unbalance taking into account the errors of measuring transformers of current has been studied with the aid of the method of numerical experiment. It is demonstrated that in a lot of cases of arch short circuits in the loaded power line and in idle mode, the control only asymmetry is insufficient for reliable determination of the type of damage. A better algorithm has been proposed for determining phase-to-phase short circuit based on the control and the analysis of the two relative unbalance currents determined by the current values of the differences of the phase currents of the line. Its serviceability was evaluated. It was found out that in all the modes being considered, the proposed method – when boundary conditions are properly chosen – makes it possible to fix three-phase and two-phase short circuit on the protected line, and in the area of remote redundancy. The dynamic properties of the proposed method are investigated for different modes of the line. It is established that in the worst case, the determining of the damage is provided during the time not exceeding 25 ms.